2023
DOI: 10.1002/jctb.7480
|View full text |Cite
|
Sign up to set email alerts
|

Critical roles of Co‐doped g‐C3N4/Bi2WO6 in photocatalytic removal of organic pollutants and treating oil field wastewater in electrocatalysis‐microbial fuel cells

Yukuan Duan,
Chen Wang,
Shilong Yang
et al.

Abstract: BACKGROUNDPhotocatalysts with Z‐type heterojunction structures for organic pollutant removal are prospective in environmental advanced oxidation processes. Introducing single metal atom to the heterojunction can further improve the synergistic activity of photocatalysts, so we doped Co single metal atom in g‐C3N4/Bi2WO6 Z‐type heterojunction.RESULTSFor this aim, a simple calcination and hydrothermal method was used to dope single atom Co on top of the Z‐type 10 wt% g‐C3N4/Bi2WO6 heterojunctions which we had te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…However, when 1, 4‐benzoquinone, 1 mmol L −1 (BQ) was added, the degradation rate of RhB was significantly reduced to only 53%, and the degradation rate constant was only 0.007 min −1 , indicating that O 2 − played an important role in the oxidation process of RhB. Therefore, the active species capture experiments indicated that O 2 − and • OH were the two main active species in the RhB degradation process 62‐73 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when 1, 4‐benzoquinone, 1 mmol L −1 (BQ) was added, the degradation rate of RhB was significantly reduced to only 53%, and the degradation rate constant was only 0.007 min −1 , indicating that O 2 − played an important role in the oxidation process of RhB. Therefore, the active species capture experiments indicated that O 2 − and • OH were the two main active species in the RhB degradation process 62‐73 …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the active species capture experiments indicated that O 2 − and • OH were the two main active species in the RhB degradation process. [62][63][64][65][66][67][68][69][70][71][72][73] Based on the above results, a schematic diagram of the photocatalytic degradation mechanism of RhB under visible-light irradiation by Bi 2 MoO 6 nanopiece@g-C 3 N 4 nanoflake composite shown in Fig. 10 was proposed.…”
Section: Study On Single-factor Conditions Of Photocatalysismentioning
confidence: 99%